Survival to hospital discharge with biphasic fixed 360 joules versus 200 escalating to 360 joules defibrillation strategies in out-of-hospital cardiac arrest of presumed cardiac etiology. (March 2019) - Olsen, Jan-Aage; Brunborg, Cathrine; Steinberg, Mikkel; Persse, David; Sterz, Fritz; Lozano, Michael; Westfall, Mark; van Grunsven, Pierre M.; Lerner, E. Brooke; Wik, Lars
Abstract: Introduction: Guidelines recommend constant or escalating energy levels for shocks after the initial defibrillation attempt. Studies comparing survival to hospital discharge with escalating vs fixed high energy level shocks are lacking. We compared survival to hospital discharge for 200 J escalating to 360 J vs fixed 360 J in patients with initial ventricular fibrillation/pulseless ventricular tachycardia in a post-hoc analysis of the Circulation Improving Resuscitation Care trial database. Methods and Results: Pre-shock rhythm, rhythm 5 s after shock, shock energy levels, termination of ventricular fibrillation/pulseless ventricular tachycardia (TOF), and survival to hospital discharge were recorded. Association between defibrillation strategy and survival to hospital discharge was investigated with multivariable logistic regression. The escalating energy group included 260 patients and 883 shocks vs 478 patients and 1736 shocks in the fixed-high energy group. There was no difference in survival to hospital discharge between escalating (70/255 patients, 28%) and fixed energy group (132/478 patients, 28%) (unadjusted OR 1.00, 95% CI 0.72–1.42 and adjusted OR 0.81, 95% CI 0.54–1.22, p = 0.32). First shock TOF was 86% in the escalating group compared to 83% in the fixed-high group, p = 0.27. Conclusion: There was no difference in survival to hospital discharge or the frequency of TOF between escalating energy and fixed-high energy group. ClinicalTrials.gov Identifier: NCT00597207.